f(x)=ln(8x)

Simple and best practice solution for f(x)=ln(8x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(x)=ln(8x) equation:


Simplifying
f(x) = ln(8x)

Multiply f * x
fx = ln(8x)

Remove parenthesis around (8x)
fx = ln * 8x

Reorder the terms for easier multiplication:
fx = 8ln * x

Multiply ln * x
fx = 8lnx

Solving
fx = 8lnx

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by 'x'.
f = 8ln

Simplifying
f = 8ln

See similar equations:

| 25a-8b+4c-6a+13b-c= | | 2a+12+a+(3a-9)=117 | | 6-18=m-4+14 | | (-3x^2-2x-2)+(2x^2+4x+4)= | | 9p-4p=-7 | | 27=3/7+6 | | 9x-4=65 | | 6+c=18 | | 3w+15=-4(w-2) | | 3w+15=-(w-2) | | 5-(1-x)=20 | | 7x+5y=-16 | | x=3(y/9) | | (4x^2+3x-5)(2x^3-10x+11)= | | 6x-15=6x | | 2x+7=10x+9 | | a-4/9a=-7/9 | | 1/2x^3-1/2x^2-24=0 | | 7=-2n-5 | | p(x)-750x^2+15000x=0 | | 0.8(25m-20n)= | | 5(2n-1)=5 | | -6+2t=3t-(6+5) | | 3x=y/9 | | ((d-4)/4)^2=49 | | -102=-6(8n+1) | | 2(3-6n)=102 | | 3[m+(-5)]=2m+10 | | 30+-10= | | 5-4(8x-2)=0 | | -5x+5(8x-6)=180 | | A=7/4 |

Equations solver categories